Simulation of phase stability at the flat top of the clic drive beam - Gerbershagen, A; Schulte, D; Burrows, P (2011)
The drive beam phase stability is one of the critical issues of the Compact Linear Collider (CLIC). In this paper the generation and propagation of drive beam phase errors is studied for effects that vary during the drive beam pulse. This includes the influence of drive beam current and phase errors as well as of drive beam accelerator RF phase and amplitude errors on the drive beam phase after the compressor chicanes and the analysis of the propagation of these errors through the drive beam combination scheme. The impact of the imperfections on the main beam is studied including the possible correction with help of a feed forward system. Copyright © 2011 by IPAC'11/EPS-AG.